A baenid turtle shell from the Mesaverde Formation (Campanian, Late Cretaceous) of Park County, Wyoming, USA - Wu, Ka Yan; Heuck, Jared; Varriale, Frank J.; Farke, Andrew (Peer Community Journal)

(untitled)
The Mesaverde Formation of the Wind River and Bighorn basins of Wyoming preserves a rich yet relatively unstudied terrestrial and marine faunal assemblage dating to the Campanian. To date, turtles within the formation have been represented primarily by isolated fragments diagnostic only to broader clades. A baenid specimen from the lower third of the Mesaverde Formation in the northwestern Bighorn Basin of Park County, Wyoming, includes a partial carapace and plastron and is the most complete turtle specimen yet described from the formation. The entire carapace would have been around 450 mm long and 380 mm wide, indicating a fairly large individual. The preserved portions of the carapace are smooth and unornamented, and the overall oval dorsal profile of the shell is similar to taxa such as Neurankylus spp. The anterior plastral lobe in the new specimen is squared off in profile as seen in Neurankylus spp., unlike the more rounded or triangular condition in Boremys spp., Eubaena hatcheri, and Baena spp., among others. The likely omega-shaped femoral-anal sulcus differs from the condition in Neurankylus spp., better matching the condition seen in many (but not all) Baenodda, although only one half of the fossil preserves the sulcus, and it may lie within expected variation for Neurankylus. Based on the overall combination of features in this Mesaverde Formation specimen, we tentatively assign it to Neurankylus sp., the first report for this taxon as well as Baenidae in the Mesaverde Formation of the Bighorn Basin.